MALDI-TOF/MS identification of species from the Acinetobacter baumannii (Ab) group revisited: inclusion of the novel A. seifertii and A. dijkshoorniae species. (March 2017) - Marí-Almirall, M.; Cosgaya, C.; Higgins, P.G.; Van Assche, A.; Telli, M.; Huys, G.; Lievens, B.; Seifert, H.; Dijkshoorn, L.; Roca, I.; Vila, Jordi
Abstract: Objectives: Rapid identification of Acinetobacter species is critical as members of the A. baumannii (Ab) group differ in antibiotic susceptibility and clinical outcomes. A. baumannii, A. pittii, and A. nosocomialis can be identified by MALDI-TOF/MS, while the novel species A. seifertii and A. dijkshoorniae cannot. Low identification rates for A. nosocomialis also have been reported. We evaluated the use of MALDI-TOF/MS to identify isolates of A. seifertii and A. dijkshoorniae and revisited the identification of A. nosocomialis to update the Bruker taxonomy database. Methods: Species characterization was performed by rpoB -clustering and MLSA. MALDI-TOF/MS spectra were recovered from formic acid/acetonitrile bacterial extracts overlaid with α-cyano-4-hydroxy-cinnamic acid matrix on a MicroflexLT in linear positive mode and 2000–20 000 m/z range mass. Spectra were examined with the ClinProTools v2.2 software. Mean spectra (MSP) were created with the BioTyper software. Results: Seventy-eight Acinetobacter isolates representative of the Ab group were used to calculate the average spectra/species and generate pattern recognition models. Species-specific peaks were identified for all species, and MSPs derived from three A. seifertii, two A. dijkshoorniae, and two A. nosocomialis strains were added to the Bruker taxonomy database, allowing successful identification of all isolates using spectra from either bacterial extracts or direct colonies, resulting in a positive predictive value (PPV) of 99.6% (777/780) and 96.8% (302/312), respectively. Conclusions: The use of post-processing data software identified statistically significant species-specific peaks to generate reference signatures for rapid accurate identification of species within the Ab group, providing relevant information for the clinical management of Acinetobacter infections.